2002
DOI: 10.1080/00207450290025644
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Attention Disorders With Measures of Neurocognitive Functioning

Abstract: The validity of the Differential Ability Scales (DAS; Elliott, 1990) in predicting attention disorders in school-aged children was examined. The participants were 40 children diagnosed with attention deficit/hyperactivity disorder (ADHD) and 40 normal children between 7 and 12 years of age. Comorbidity was controlled by excluding children with ADHD who had a concurrent DSM-IV diagnosis such as reading disability, learning disability, mood disorder, or behavioral disorder. In addition, groups did not differ sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Although the DAS has been found to be a reliable cognitive measure in differentiating children with LD from controls, it has not been found in this investigation to be as robust in differentiating children with ADHD from controls. Some scale score differences were found between samples that were supported by previous research (i.e., Gibney et al, 2002).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although the DAS has been found to be a reliable cognitive measure in differentiating children with LD from controls, it has not been found in this investigation to be as robust in differentiating children with ADHD from controls. Some scale score differences were found between samples that were supported by previous research (i.e., Gibney et al, 2002).…”
Section: Discussionsupporting
confidence: 83%
“…The ADHD group demonstrated a weakness on RDIG and a competency on ROIMM as compared to controls. However, Gibney et al (2002) reported significant group differences on the Nonverbal Reasoning Cluster and the GCA. Although the noted competency in ROIMM was not supported in Gibney's et al study, previous research has found ADHD samples to perform better on visually oriented tasks.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Among the measures appropriate for such assessment is the Comprehensive Test of Phonological Processing (CTOPP; Wagner, Torgesen, & Rashotte, 1999). Elliott, 1990) Relative to normal controls, low scores on the Sequential and Quantitative Reasoning, and Recall of Digits subtests (Note: subjects, 63% combined type; Gibney, McIntosh, Dean, & Dunham, 2002).…”
Section: Fig 61 (Continued)mentioning
confidence: 99%
“…The recently revised Differential Abilities Scales-Second Edition (DAS-II; Elliott, 2007) and its predecessor are popular measures of intellectual and cognitive functioning among school psychology practitioners and have excellent technical qualities (Dumont, Willis, & Sattler, 2001;Elliott, 2007;Platt, Kamphaus, Keltgen, & Gilliland, 1991). The Verbal (Gc), Nonverbal Reasoning (Gf), and Spatial (Gv) abilities factor structure hypothesized for the DAS and DAS-II Core subtests has been validated using large standardization samples (Elliott, 1990(Elliott, , 2007; children with cultural, linguistic, or racial differences (DiCerbo & Barona, 2000;Keith, Quirk, Schartzer, & Elliott, 1999;Riccio, Ross, Boan, Jemison, & Houston, 1997); and children with developmental and learning disabilities (Dumont, Cruse, Price, & Whelley, 1996;Elliott, 2001;Gibney, McIntosh, Dean, & Dunham, 2002;Hughes & McIntosh, 2002;Kercher & Sandoval, 1991;McIntosh & Gridley, 1993;Shapiro, Buckhalt, & Herod, 1995). The structure is also supported by independent exploratory and confirmatory factor analysis (Daleo et al, 1999;Dunham, McIntosh, & Gridley, 2002;Keith, 1990).…”
Section: Empirical Examination Of the Differential Ability Scalesmentioning
confidence: 99%